effect of verapamil on in vitro susceptibility of promastigote and amastigote stages of Leishmania tropica to meglumine antimoniate - Shokri, Azar; Sharifi, Iraj; Khamesipour, Ali; Nakhaee, Nozar; Fasihi Harandi, Majid; Nosratabadi, Jafar; Hakimi Parizi, Maryam; Barati, Mohammad (Parasitology research (1987), 2012)
Pentavalent antimonials are the standard treatment for cutaneous leishmaniasis (CL) with low efficacy and resistance is emerging. CL is increased significantly in respect to incidence rate and expanding to new foci. In the present study, the effect of verapamil on in vitro susceptibility of promastigote and amastigote stages of Leishmania tropica to meglumine antimoniate (MA, Glucantime) was evaluated using colorimetric assay (MTT) and in a macrophage model, respectively. Verapamil, as a calcium channel blocker, affects drug uptake by preventing of drug efflux from the cells. In promastigote form, several concentrations of MA with or without verapamil showed significant decrease (P < 0.05) in optical density. The overall mean IC50 value with combination of MA plus verapamil (IC50 = 116.03 μg/ml) was significantly less than MA (IC50 = 225.14 μg/ml) alone (P < 0.05) for promastigote stage. Similarly, the amastigote stage was more susceptible to treatment with MA plus verapamil to that of MA alone (P < 0.05). Analysis of overall effect of different concentrations of MA alone, compared with combination of MA plus verapamil by mean infection rate of amastigotes in each macrophage showed a significant difference (P < 0.05).These findings indicated some degree of synergistic effects between MA and verapamil on in vitro susceptibility of L. tropica to MA. Further works are required to evaluate this synergistic effect on animal model or volunteer human subjects.